Analisis Sistem Pengendalian Internal pada Penerimaan Kas dan Verifikasi Invoice pada Hotel XYZ - Salsabila, Devana; Islamudin, Ardhi (Lembaga Pengembangan Kinerja Dosen, 2025)
Cash receipts represent one of the essential components for the hospitality industry. Hotels generate revenue primarily through room rentals, the use of available facilities, as well as the sale of food and beverages provided in their in-house restaurants. This study aims to understand how the internal control system is implemented in managing cash receipts and verifying invoices at Hotel XYZ. This research adopts a qualitative method with a descriptive analytical approach. The descriptive analysis in this study involves presenting data in the form of verbal descriptions, images, or graphics. Based on the analysis using the COSO framework, the results indicate that elements such as the control environment and control activities have been implemented effectively and optimally. However, the analysis also reveals that the risk assessment component within the cash receipt process has not yet been fully optimized, indicating a need for additional training and improvement in that area.